Avaliação do Risco Ambiental de Resíduos Gerados pela Suinocultura em Modelos vegetais e ao Ambiente, Por Meio de Análises Toxicogenéticas, Biomarcadores Bioquímicos, Crescimento E trocas Gasosas. - Aragão, Francielen Barroso (2021)
The inadequate management of residues from swine production can cause contamination of water courses, soil and air, representing a risk to the environment. The objective of this work was to evaluate the environmental risk of the raw residue and effluent from the stabilization pond of swine biodigester, to evaluate the reuse of the effluent from the stabilization pond as a biofertilizer and the quality of water samples from the Santa Maria do Doce River, in the around the pig farm. The effluents from the swine biodigester (raw and stabilization pond waste) and river water samples were collected in the municipality of Santa Tereza-ES, Brazil. From these samples, chemical characterization and laboratory tests were carried out. Dilutions were carried out from the pure effluents (C1), and successive reductions were made in the amount of effluent, 50% (C2), 25% (C3), 12.5% (C4), 6.25% (C5), 3.12% (C6), 0.78% (C7) and 0.39% (C8). The river samples were collected in two campaigns (highest and lowest rainfall), in 3 sampling stations: upstream from the swine farm (EA1), close to the swine farm (EA2) and downstream from the swine farm (EA3). Seeds of Lactuca sativa and Allium cepa were germinated in the treatments, and the following parameters were evaluated: germination, root growth, evaluation of toxicogenetic potential and analyzes of the activity of enzymes SOD, CAT, GST and quantification of GSH and LPO. Dilutions from the stabilization pond were used to evaluate the effluent as a biofertilizer in corn plants, through gas exchange and growth analyses. For this evaluation, two controls were used: a treatment containing only water and a treatment with commercial fertilizer. All data were submitted to ANOVA, followed by the Kruskal Wallis or Tukey mean test (p<0.05). The results demonstrate that the two effluents inhibited the germination of L. sativa and A. cepa, in addition to reducing root growth, and promoting higher frequencies of chromosomal alterations in the other concentrations. The observed damages are possibly related to the heavy metals found in the studied samples. The river samples showed a reduction in the mitotic index in EA2 and EA3 (second campaign) in A. cepa compared to the negative control. And in both models, there was an increase in chromosomal alterations (EA2 and EA3). The damages observed are possibly related to the excess of aluminum found in the samples, human activity in the surroundings of the river, the dumping of effluents from pig farming and domestic sewage. The maize plants submitted to treatments with effluents, when compared to the water control, showed a significant increase in biomass, but higher effluent concentrations prevented seed germination. Possibly the excess of K and Na may have caused water stress in the seeds, preventing germination and development of plants, in which the dilution of the effluent reduced the effects of excess K and Na and, consequently, reduced the availability of other essential nutrients for the corn plants.